1998
DOI: 10.4141/s97-030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil compaction and chipped aspen residue on aspen regeneration and soil nutrients

Abstract: Effects of soil compaction and chipped aspen residue on aspen regeneration and soil nutrients. Can. J. Soil Sci. 78: 85-92. The effects of soil compaction and depth of chipped aspen residue on aspen regeneration, plant community development, decomposition, and nutrient cycling were tested on an Orthic Gray Luvisol in the Lower Foothills of Alberta. Twenty-seven 100-m × 15-m plots were established in 1992. Three depths of chipped aspen residue (0, 1-5 cm and >10 cm) and three levels of compaction (no compaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 11 publications
(3 reference statements)
3
18
1
Order By: Relevance
“…On the surface (0-10 cm) of the Freest plots soil had recovered to near predisturbance levels in the herbicide-treated, severely compacted plots (p = 0.0482; 2% higher than preharvest). Although there was no significant herbicide effect at the other sites, the level of recovery at these study sites after 5 years was unexpected, since many authors report a return to the initial, uncompacted state is often slow or nonexistent (Hatchell et al 1970;Froehlich and McNabb 1984;Corns and Maynard 1998;Stone and Elioff 1998). Recovery to preharvest levels on these LTSP sites can be attributed to a host of environmental factors such as high rock-fragment content, a fluctuating water table, or freeze-thaw cycles (Fleming et al 1998;Stone and Kabzems 2002).…”
Section: Five-year Recoverymentioning
confidence: 81%
“…On the surface (0-10 cm) of the Freest plots soil had recovered to near predisturbance levels in the herbicide-treated, severely compacted plots (p = 0.0482; 2% higher than preharvest). Although there was no significant herbicide effect at the other sites, the level of recovery at these study sites after 5 years was unexpected, since many authors report a return to the initial, uncompacted state is often slow or nonexistent (Hatchell et al 1970;Froehlich and McNabb 1984;Corns and Maynard 1998;Stone and Elioff 1998). Recovery to preharvest levels on these LTSP sites can be attributed to a host of environmental factors such as high rock-fragment content, a fluctuating water table, or freeze-thaw cycles (Fleming et al 1998;Stone and Kabzems 2002).…”
Section: Five-year Recoverymentioning
confidence: 81%
“…The density of aspen suckers is conditioned by mortality of parent trees, i.e., loss of apical dominance (Peterson and Peterson 1992), but sucker growth or height is more closely related to light conditions (Huffman et al 1999). Compaction and associated soil physical disturbances can stimulate suckering (Corns and Maynard 1998), but compaction has been shown to be limited to the wheel track area of cutovers (Brais and Camiré 1998) and would have affected only 5% of the total area under partial harvesting treatments. The decrease in correlation between sky openness and live aspen biomass observed during the second growing season after harvesting indicated that other factors were affecting sucker growth or survival; among these factors, the most noticeable was the presence of leaf and twig blight (Venturia populina (Vuill.))…”
Section: Vegetation Responsementioning
confidence: 99%
“…Swellingshrinking, freezing-thawing, root activity and organic matter are natural factors that can ameliorate soil compaction (Larson and Allmaras 1971), but freezing-thawing is thought to be the major factor in boreal forest soils (McNabb 1994). Natural recovery of compacted soil in Alberta boreal forests required only 3 to 10 yr (Corns 1988;Corns and Maynard 1998) but in other cold environments, recovery has taken longer (Blake et al 1976;Voorhees and Sharratt 1997). Forest soils in Alberta have recovered more rapidly when tillage enhanced the freeze-thaw process (McNabb 1994 For personal use only.…”
mentioning
confidence: 99%